2014
DOI: 10.1111/ijac.12251
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation Resistance of AlPO4 Bonded Ceramic Coating Formed on Titanium Alloy for High‐Temperature Applications

Abstract: AlPO4 based coatings were prepared on Ti‐6Al‐2Zr‐1Mo‐1V titanium alloy using aluminum phosphate as a binder and Al2O3/Cr2O3 based mixing particles as the fillers. The microstructure, phase and chemical composition of the coatings were analyzed by SEM, XRD and EDS techniques. The high temperature infrared emissivity values of coated and uncoated titanium samples were tested. The results show that the coating had a higher infrared emissivity value (>0.8) than titanium substrate (0.15–0.3) in the wide wavelength … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 28 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…It should be noted that AlPO 4 cannot be used as the dominate material of coatings. Because a great shrinkage will be usually caused by the dehydration and phase transition of AlPO 4 , leading to a loose porous structure, which cannot prevent deuterium permeation 41,42 . Deuterium permeability of the α‐Al 2 O 3 /AlPO 4 coating is 1.42 × 10 −15 mol/(m s)/Pa 0.5 at 400°C and 1.32 × 10 −15 mol/(m s)/Pa 0.5 at 450°C.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that AlPO 4 cannot be used as the dominate material of coatings. Because a great shrinkage will be usually caused by the dehydration and phase transition of AlPO 4 , leading to a loose porous structure, which cannot prevent deuterium permeation 41,42 . Deuterium permeability of the α‐Al 2 O 3 /AlPO 4 coating is 1.42 × 10 −15 mol/(m s)/Pa 0.5 at 400°C and 1.32 × 10 −15 mol/(m s)/Pa 0.5 at 450°C.…”
Section: Resultsmentioning
confidence: 99%
“…Because a great shrinkage will be usually caused by the dehydration and phase transition of AlPO 4 , leading to a loose porous structure, which cannot prevent deuterium permeation. 41,42 Deuterium permeability of the α-Al 2 O 3 /AlPO 4 coating is 1.42 × 10 −15 mol/(m s)/Pa 0.5 at 400 • C and 1.32 × 10 −15 mol/(m s)/Pa 0.5 at 450 • C. Accordingly, the PRF is 915 at 400 • C and 1935 at 450 • C, which means the α-Al 2 O 3 /AlPO 4 coating enhanced the deuterium resistance of the substrate by above three orders of magnitude. Even though deuterium permeability of the α-Al 2 O 3 /AlPO 4 coating is similar to each other at 400 and 450 • C, the permeability of the substrate at 450 • C is above two times that at 400 • C, leading to a significant increase in PRF value from 915 to 1935 on the basis of Equation ( 2).…”
Section: Deuterium Permeation Reduction Of the α-Al 2 O 3 Composite C...mentioning
confidence: 99%
“…The authors examined the effect of this process on the biocompatibility of Ti-6Al-4V alloy and found that a micro rough surface of TiO2 can significantly improve the biocompatibility properties of the alloy texture. However, Ti-6Al-4V alloy possesses low hardness and high susceptibility to oxidation, in effect, limiting its viability in high temperature applications [7][8][9][10]. Notwithstanding, this alloy has essential bulk properties which are useful in various applications and a possible solution to its limitations is to protect the surface from being exposed to stringent high temperatures.…”
Section: 0introductionmentioning
confidence: 99%